American women in the Progressive Era, 1900-1920 - Schneider,Dorothy (Anchor Books, 1993)
The period known as the Progressive Era, from 1900 to 1920, was one of radical change in America, particularly for women. The era saw the start and resolution of "the war to end war," the height of the temperance movement, and the heyday of muckraking journalism, and it culminated in the passage of the 19th Amendment, giving American women the right to vote. American Women in the Progressive Era ties together all of the movements, moods, and milestones of this exciting period of change in America. It explores the role of American women in World War I, the labor movement, and the struggle to win the vote, and it describes how women of all ethnic and social backgrounds were affected by their changing roles in these and other areas. To read the story of American women in the first two decades of the 20th century is to explore a period of change, as massive immigration, industrialization, and urbanization transformed the country. It is to learn of women coping with the changes so created, and of women themselves changing, moving more and more from the private to the public sphere. New labor-saving household devices freed women for paid or volunteer work outside their homes, and they began to see their responsibility to make not only their homes but also their communities, their states, even their nation fit places in which to live and raise children. In the process, millions of them discovered how much they needed and wanted the vote. This book describes in words and in pictures what was happening in the domestic lives of ordinary women, in their working lives (in and out of their homes), and in the ways they were expanding their roles, during a period bright with hope for a brave new world and distinguished by cross-class cooperation among women all over the nation. Readers will enjoy this thoroughly researched, lively book on women and their startling range of activities in the Progressive Era. American Women in the Progressive Era incorporates the words and experiences of individual women as found in biographies, diaries, letters, memoirs, and women's magazines from that period. The book brings alive a period of rich social history and provides the reader with a sense of what it was like for women at that time. The reference value of the book is enhanced by extensive source notes, a bibliography, and a complete index. Numerous historical photographs illustrate the text.